2014
DOI: 10.1007/s00167-014-2934-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of knee stability and joint degeneration for double- and single-bundle ACL reconstruction

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 38 publications
1
48
0
3
Order By: Relevance
“…[47][48][49] The changes in the contact area and pressure after SB ACL reconstruction may be one of the causes of OA, and DB ACL reconstruction may reduce the incidence of OA by closely restoring contact area and pressure. 48 In their study, 29 Sun et al found that 29.2% of patients in the DB Auto group and 27.3% of patients in the DB Allo group had a progression in arthritic changes. In our study, 11.3% (7 of 62) of patients in the Auto group and 11.9% (7 of 59) of patients in the Allo group had an arthritic progression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[47][48][49] The changes in the contact area and pressure after SB ACL reconstruction may be one of the causes of OA, and DB ACL reconstruction may reduce the incidence of OA by closely restoring contact area and pressure. 48 In their study, 29 Sun et al found that 29.2% of patients in the DB Auto group and 27.3% of patients in the DB Allo group had a progression in arthritic changes. In our study, 11.3% (7 of 62) of patients in the Auto group and 11.9% (7 of 59) of patients in the Allo group had an arthritic progression.…”
Section: Discussionmentioning
confidence: 97%
“…The authors suggested the fresh-frozen hamstring tendon allograft as a reasonable alternative choice to the autograft for ACL reconstruction. Sun et al 29 also reported their clinical outcomes of DB ACL reconstruction with an autograft and allograft. However, the DB reconstruction technique they adopted was not anatomic reconstruction.…”
mentioning
confidence: 94%
“…In another randomized clinical trial, Ran Sun and colleagues compared double bundle ACL reconstruction using either allograft or auto graft with single bundle ACL reconstruction. Based on the IKDC score and Lysholm score, there were no significant difference between these three groups, but they showed better anterior and rotational stability with a lower rate of arthritic progression and tunnel expansion in double bundle ACL reconstruction than single bundle procedure (16). …”
Section: Discussionmentioning
confidence: 87%
“…Another randomized prospective controlled study published by Sun et al in 2015 shows that double-bundle ACL restoration increases the anterior and rotational stability, and presents a decreased progression towards arthritis and tunnel growth compared to single-bundle at 3 years after the surgery. [33][34][35] In conclusion, studies have suggested that the anatomical double-bundle method could provide improved stability to ACL-deficient knees immediately after surgery. Kinematic performance was improved in cases with double-bundle ACL reconstruction.…”
Section: Resultsmentioning
confidence: 99%